Unusual-massive acromioclavicular joint cyst associated with complete reabsorption of the humeral head in outcomes of long-standing surgical stabilization for recurrent dislocations: case report - Giardini, Piero; Mirabassi, Nicola; Dalvit, Leonardo; Christodoulidis, Avraam; Molinari, Marco (Lo Scalpello - Journal, 2022)
Introduction. Acromioclavicular joint cysts (AJC) are rare findings associated with acromioclavicular (AC) joint arthritis or rotator cuff tear arthropathy. AJC type 1 are very rare and caused by an advanced degenerative arthritic process of the AC joint alone, without a rotator cuff tear; AJC Type 2 cysts are associated with a massive rotator cuff tear. Surgical excision represents the treatment of choice, since the aspiration of the cyst and the contextual injection of corticosteroid is burdened by a high rate of recurrence. We report the case of an unusual-massive acromioclavicular joint cyst associated with complete reabsorption of the humeral head and outcomes of long-standing surgical stabilization for recurrent dislocations. Case presentation. An 83-year-old man presented to our outpatient clinic complaining of a large cystic mass over the right shoulder region. Clinical examination revealed a mass over the right AC Joint, tender on palpation with normal overlying skin. Active range of motion (ROM) was limited but did not cause any discomfort to the patient. Imaging revealed complete reabsorption of the humeral head, and advanced shoulder degenerative arthropathy with loosening of the implanted hardware. Magnetic resonance imaging (MRI) revealed a ganglion cyst with the pathognomonic Geyser sign. The patient underwent surgical excision of the mass and an excision of 1 cm of the distal clavicle was performed to reduce the risk of recurrence. After one year of follow-up the patient is asymptomatic with no signs of recurrence. Discussion. Acromion-clavicular joint cysts are a rare consequence of advanced AC joint arthritis or chronic rotator cuff tear. The case presented is particularly interesting since it describes an AJC associated with an end stage shoulder arthropathy as a result of a surgical treatment for shoulder instability of only historical interest and certainly very rare to encounter in current clinical practice. Complete reabsorption of the humeral head associated with the mobilization of the implanted pins resulted in the formation of a fibrous cystic mass that replaced the head of the humerus; a complete cuff tear and a defect in the inferior capsule of the AC joint led to leakage of the synovial fluid through the AC joint which formed a cyst that appeared to be communicating through an isthmus with the previous described subacromion cyst. For the aforementioned reasoning, we believe that the formation of the acromioclavicular cyst is strictly related to the outcome of the previous surgery and represents the novelty of the case presented. Because of age, low demands and few symptoms lamented by the patient, we considered to perform only excision of the mass and resection of distal clavicle; patient satisfaction and no recurrence of the cyst after one year of follow-up rendered the therapeutic choice satisfying. Clinical presentation, instrumental diagnosis, and therapeutic possibilities on AJC are not discussed in detail as they do not represent the specific interest of the case and are debated in several other case reports. Conclusions. Although rare findings, AJC can be encountered in clinical practice in patients affected by degenerative shoulder arthropaties. Surgical excision associated with lateral end clavicle resection is a viable therapeutic option to treat an AJC in the elderly, which resulted in an appropriate treatment of the mass with no sign of recurrence after one year of follow up in the case presented.